2009
DOI: 10.1016/j.bandl.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding in an instant: Neurophysiological evidence for mechanistic language circuits in the brain

Abstract: How long does it take the human mind to grasp the idea when hearing or reading a sentence? Neurophysiological methods looking directly at the time course of brain activity indexes of comprehension are critical for finding the answer to this question. As the dominant cognitive approaches, models of serial/cascaded and parallel processing, make conflicting predictions on the time course of psycholinguistic information access, they can be tested using neurophysiological brain activation recorded in MEG and EEG ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
170
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(206 citation statements)
references
References 177 publications
33
170
0
Order By: Relevance
“…Further evidence for this assumption comes from the famous shadowing task by Marslen-Wilson (1973, 1985, in which people were able to repeat another speaker's sentences with a time delay of only 250 ms. Finally Pulvermüller resumes that early indexes of lexical, syntactic and semantic processes have been found after 100-250 ms in written and spoken language processing which reflects almost parallel processes (Pulvermüller, 2005;Pulvermüller et al, 2009). Both behavioural studies (Marslen-Wilson, 1985) as well as the results of the underlying functional neuroanatomical studies are therefore roughly comparable to the observed behavioural inter-turn delays of about 120-250 ms.…”
Section: Realistic Time Frames For Turn-end-detectionsupporting
confidence: 64%
“…Further evidence for this assumption comes from the famous shadowing task by Marslen-Wilson (1973, 1985, in which people were able to repeat another speaker's sentences with a time delay of only 250 ms. Finally Pulvermüller resumes that early indexes of lexical, syntactic and semantic processes have been found after 100-250 ms in written and spoken language processing which reflects almost parallel processes (Pulvermüller, 2005;Pulvermüller et al, 2009). Both behavioural studies (Marslen-Wilson, 1985) as well as the results of the underlying functional neuroanatomical studies are therefore roughly comparable to the observed behavioural inter-turn delays of about 120-250 ms.…”
Section: Realistic Time Frames For Turn-end-detectionsupporting
confidence: 64%
“…From a dual-route perspective of reading (Coltheart, 2007;Coltheart, Rastle, Perry, Langdon, & Ziegler, 2001), less effort was expected in order to find a fitting orthographic representation for familiar words in the orthographic lexicon, whereas the search should be prolonged and unsuccessful in case of unfamiliar word-forms, resulting in enhanced N1-amplitudes to pseudohomophones and pseudowords as found by us. Here the finding that lexical variables affect the brain response very early in processing fits better within frameworks where word recognition is accomplished by early near-simultaneous (cascaded) or partially overlapping stages and the underlying processes can be interactive (e.g., o Grainger & Holcomb, 2009;Pulvermüller, Shtyrov, & Hauk, 2009). Accordingly, in a study using a multiple regression design Hauk, Davis et al (2006) reported an early lexical frequency effect around 110 ms that closely follows and partly overlaps with the earlier bigram frequency effect.…”
Section: Discussionmentioning
confidence: 98%
“…The interaction, though, was relatively weak in the global analyses and occurred only in a brief interval on a deflection that was absent in Experiments 1 and 2. Yet, there are reasons to take this finding serious: First, it is well known that effects in early time ranges are generally small and focal, so that rather mild amplitude modulations are expected (Penolazzi et al, 2007;Pulvermüller, Shtyrov, & Hauk, 2009). Second, the effect is only weak in a conservative analysis including all channels, whereas post-hoc tests on averaged channels PO7/8 revealed a very robust pattern.…”
Section: Comparison Between Experiments)mentioning
confidence: 95%